(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative condition for which there is no single diagnostic test or biomarker. These is necessity to identify reliable biomarkers of ALS progression for clinical practise. Plasma creatinine has been described as a prognostic biomarkers for ALS patients Objective: The purpose of the present study was to determine the association of serum creatinine in patients with amyotrophic lateral sclerosis. Methodology: This analytical cross-sectional study was conducted in the Department of Neurology at Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2019 to December 2020 for a period of two years. The amyotrophic lateral sclerosis patients were enrolled in group I and age and gender matched healthy control were enrolled in group II. Clinical variables were obtained from the ALS patients and control groups including age, sex, BMI, site of onset, disease duration and other relevant information. Focused and detailed neurological examination was performed in each of the participants. Revised ALS functional rating scale (ALS-FRS) was also performed for functional assessment. Venous blood samples were collected for serum creatinine investigations. Results: A total number of 70 patients were enrolled for this study of which 35 cases of ALS were in group I and the rest of 35 healthy participants were in group II. The mean age was 52.8±12.73 years in group I and 53.57±6.56 years in group II. More than half (51%) patients had serum creatinine level less than 0.8 mg/dL in group I and not found in group II. The mean serum creatinine was 0.76±0.17 mg/dl in group I and 1.03±0.12 mg/dl in group II (p=0.01). The mean ALS-FRS was 26.88±4.88 in serum creatinine less than 0.60 (mg/dL), 26.83±3.81 in serum creatinine 0.61-0.79 (mg/dL), 30.38±5.3 in serum creatinine 0.80 to 1.00 (mg/dL) and 36.0±2.83 in serum creatinine more than 1.00 (mg/dL) (p<0.01). The mean serum creatinine was 0.72±0.13 (mg/dL) in limb onset, 0.73±0.15 (mg/dL) in bulbar onset and 0.95±0.08 (mg/dL) in mixed (p<0.01). Conclusion: Serum creatinine level is significantly lower in amyotrophic lateral sclerosis patients and low serum creatinine significantly associated with increased severity of the disease as well as pattern of onset of the disease and ALS–FRS in patients with amyotrophic lateral sclerosis. Journal of National Institute of Neurosciences Bangladesh, January 2025;11(1):19-27